The Integration of Eco-Theology in Sekolah Alam Yogyakarta: A Living Quran: Integrasi Eco-Theology di Sekolah Alam Yogyakarta: Sebuah Living Quran - Dwi Ratnasari; Luqyana Azmiya Putri; Febri Widiandari; Adhi Setiyawan (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2024)
Purpose – This study aims to explore the integration of eco-theology in the Natural School of Yogyakarta, also known as Nurul Islam Integrated Islamic Elementary School. The research investigates how eco-theology is incorporated into the school’s activities, particularly those related to environmental awareness. Design/methods/approach – The study employs the concept of "Living Quran" which examines the Quran not merely as a textual entity but as a social phenomenon connected to its presence in specific contexts, focusing on a particular Natural School in Yogyakarta within a defined timeframe. Observations were conducted on activities directly related to the research theme, with respondents and informants unaware that they were being observed. Findings – The results indicate that Nurul Islam Natural School plays a significant role in fostering a generation that understands the interconnectedness between humans and nature. One of its programs, Outing, introduces students to nature through direct experiences. Another initiative, Family Conservation Day, encourages families to take ownership and responsibility for their surrounding environment. The Parent Market Day program allows students and their parents or guardians to participate in selling goods, with participants bringing their own products for sale. Lastly, the school organizes environmental care activities to instill a sense of responsibility toward nature. Research implications/limitations – This study demonstrates how Islamic education can integrate eco-theology through practical programs to enhance environmental awareness, transform students into agents of change, and promote a family-based collaborative approach. Originality/value – The findings provide a unique perspective on the direct implementation of Quranic values in environmental conservation within a Natural School setting, offering a novel contribution to the study of Islamic eco-theology. Abstrak Tujuan – Penelitian ini bertujuan untuk mengeksplorasi integrasi eco-theologhy di sekolah alam Yogyakarta atau dikenal juga sebagai Sekolah Dasar Islam Terpadu Nurul Islam. Penelitian ini mengeksplorasi integrasi eco-theology di sekolah alam dengan berfokus pada kegiatan-kegiatan sekolah yang berkenaan dengan kesadaran akan lingkungan hidup.  Desain/metode/pendekatan – Living Quran yang merupakan studi tentang al-Quran, tetapi tidak bertumpu pada eksistensi tekstual melainkan pada studi tentang sosial yang berhubungan dengan kehadiran al-Quran yang berfokus pada sekolah alam Yogyakarta tertentu dan mungkin masa tertentu pula. Kegiatan diamati terkhusus berhubungan dengan tema penelitian. Aktivitas ini dapat dilihat responden, informan tidak merasa bila diamati. Temuan – Hasil penelitian menunjukkan bahwa Sekolah Alam Nurul Islam dapat memainkan peran penting dalam membentuk generasi yang memahami keterkaitan antara manusia dan alam. Outing merupakan salah satu program sekolah alam yang bertujuan untuk mengenalkan siswa dengan alam. Kemudian, Family Conservation Day yang memberikan kesempatan kepada keluarga untuk mengambil kepemilikan dan tanggung jawab terhadap lingkungan di sekitar mereka. Marketday Orang Tua merupakan sebuah program berjualan yang pesertanya ialah siswa dan orang tua atau wali siswa itu sendiri. Para peserta marketday diperkenankan untuk membawa produk yang akan diperjual belikan. Terakhir ialah, aksi kepedulian lingkungan. Implikasi/batasan penelitian – Penelitian ini menunjukkan bagaimana pendidikan Islam dapat mengintegrasikan eco-theology melalui program praktis untuk meningkatkan kesadaran lingkungan, menjadikan siswa agen perubahan, dan mendorong pendekatan kolaboratif berbasis keluarga. Orisinalitas/nilai – Temuan penelitian menawarkan perspektif unik tentang implementasi langsung nilai Al-Quran dalam konservasi lingkungan di Sekolah Alam, memberikan kontribusi baru pada studi eco-theology Islam.